2016
DOI: 10.18869/modares.jcp.5.4.541
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some chemical inducers on chocolate spot disease of faba bean in Tunisia

Abstract: Botrytis fabae is one of the most important fungal pathogens attacking the leaves and the stem of faba bean Vicia faba L. and causes severe yield losses. This study was carried out to evaluate the effect of four chemical inducers (salicylic, citric, ascorbic and oxalic acids) and one fungicide (Carbendazim) against B. fabae in field and glasshouse conditions. Under field conditions for two seasons and glasshouse experiments, plants treated with salicylic acid showed substantial and significant decrease in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…SA was the most effective one, followed by ascorbic acid. Plant treatment with organic acids and calcium chloride under greenhouse and/or field conditions led to a significant effect on controlling the disease and increasing phenols content as well as the activity of oxidative enzymes [ 6 ]. The results also agreed with the results of salicylic, citric, ascorbic, and oxalic acids as effective chemical inducers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SA was the most effective one, followed by ascorbic acid. Plant treatment with organic acids and calcium chloride under greenhouse and/or field conditions led to a significant effect on controlling the disease and increasing phenols content as well as the activity of oxidative enzymes [ 6 ]. The results also agreed with the results of salicylic, citric, ascorbic, and oxalic acids as effective chemical inducers.…”
Section: Discussionmentioning
confidence: 99%
“…Chocolate spot disease of faba bean is caused by Botrytis fabae and B. cinerea and is considered the most important disease in the Northern region of the Egyptian Nile Delta [ 4 ], which has relatively low temperature and, at the same time, high relative humidity that favor the spread of this disease [ 5 ]. The disease causes a severe yield loss reaching 60–80% among the susceptible cultivars [ 6 ]. It decreases the total carbohydrates, nitrogen, nucleic acid, and protein contents of the yielded seeds [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…SA 200 ppm treatment had the highest value followed by GE 100 and OE 100 ml/L with averages of (0.821, 0.787 and 0.780), respectively. Mbazia et al (2016) found that foliar spray of faba bean with SA increased total phenols.…”
Section: Physiological Traits Effect Of Foliar Spraying Treatments Onmentioning
confidence: 98%
“…Chocolate spot, which caused by Botrytis fabae Sard., is one of the most yield limiting constraints of faba bean worldwide (Torres et al, 2004), as in the northern region of the Nile Delta of Egypt, where low temperature and high relative humidity favoring its spread are dominant (El-Banoby et al, 2013) cause severe yield losses reach 60-80% among the susceptible cultivars (Mbazia et al, 2016). It decreases the total carbohydrates, nitrogen, protein and nucleic acid (DNA and RNA) contents of yielded seeds (Aldesuquy, 2015).…”
Section: Introductionmentioning
confidence: 99%